2020
DOI: 10.11114/bms.v6i2.4899
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Resource Management Towards Employees Retention During Covid-19 Pandemic in Medical Supplies Sector - Egypt

Abstract: The introduction of the report has mentioned the aim of this research. As per the introductory part, the aim of this research paper is to examine the role of Human Resources Management (HRM) towards the employees as far as curbing the adverse impact of Covid-19 is concerned. The Literature Review has mentioned the theories of motivation that impacts on the retention level of the employees, along with the studies conducted in the same domain. Some of the studies have been included in which strategies of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 5 publications
1
48
1
1
Order By: Relevance
“…In this case, most organizations were not able to provide their employees enough information about their management plan or their intended reactions toward the pandemic (Elsafty & Ragheb, 2020), while having clear workplace guidelines during hard times helps to reduce employees' stress and to increase their motivation and confidence (Wong, Ho, Wong, Cheung, & Yeoh, 2020). The study of Elsafty and Ragheb (2020) showed that access to information and the update related to the pandemic is associated significantly with employees' retention. Nonetheless, it might be difficult to achieve it if organizations are not able to get this information, especially when they are in a reactive and survival mode, due to the novelty of this pandemic.…”
Section: Covid-19 and Strategic Human Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, most organizations were not able to provide their employees enough information about their management plan or their intended reactions toward the pandemic (Elsafty & Ragheb, 2020), while having clear workplace guidelines during hard times helps to reduce employees' stress and to increase their motivation and confidence (Wong, Ho, Wong, Cheung, & Yeoh, 2020). The study of Elsafty and Ragheb (2020) showed that access to information and the update related to the pandemic is associated significantly with employees' retention. Nonetheless, it might be difficult to achieve it if organizations are not able to get this information, especially when they are in a reactive and survival mode, due to the novelty of this pandemic.…”
Section: Covid-19 and Strategic Human Resource Managementmentioning
confidence: 99%
“…In this context, organizations that were facing financial difficulties due to this pandemic have adopted downskilling by cutting back on recruitment of high-skill jobs more than low-skill jobs, to reduce their costs and try to sustain their business (Campello et al, 2020); they have frozen or cut back all their recruitment; or they have laid off their employees (Campello et al, 2020;Giupponi & Landais, 2020). Indeed, millions of people found themselves unemployed due to the COVID-19 outbreak (Blustein et al, 2020;Elsafty & Ragheb, 2020). Cheng et al (2020) pointed out that the employment activities have increased after the companies' reopening in some US states mainly due to the return to work of employees, after lockdown, to their physical workplace.…”
Section: Staffingmentioning
confidence: 99%
“…On the way to contextual analysis of the research, Elsafty ( , 2019Elsafty ( , 2020 provided a holistic framework to analyze the case using nine elements covering the whole ecosystem of educational organization(s) and all related stakeholders, including suppliers, distributors, customers, competitors, government agencies, and so on -involved in the delivery of educational outcomes, and related service through both competition and cooperation. The nine elements framework has been used in several research papers Elsafty & AlNawaly, 2020;Elsafty & Ragheb, 2020;Elsafty & Abadir & Sharawy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The nine elements framework has been used in several research papers Elsafty & AlNawaly, 2020;Elsafty & Ragheb, 2020) as well as within professional consultancy, the framework helped diverse types of organizations (industrial, food, service, educational, trade, … etc. ) analyze their problems and properly address it in a comprehensive way to reach proper outcomes for decision making.…”
Section: Introductionmentioning
confidence: 99%